2020
DOI: 10.2174/1568026620666200102104930
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase-based Cancer Therapeutics: A Review on their Clinical Trials

Abstract: Telomeres are protective chromosomal ends that shield the chromosomes from DNA damage, exonucleolytic degradation, recombination, and end-to-end fusion. Telomerase is a ribonucleoprotein that adds TTAGGG tandem repeats to the telomeric ends. It has been observed that 85 to 90% of human tumors express high levels of telomerase, playing a crucial role in the development of cancers. Interestingly, the telomerase activity is generally absent in normal somatic cells. This selective telomerase expression has driven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 177 publications
0
28
1
Order By: Relevance
“…It has been reported that telomerase-positive tumors often exhibit shorter telomeres than normal surrounding tissue counterparts [5], as a consequence of the late reactivation of telomerase activity during tumorigenesis [11]. This observation, alongside the evidence that the enzyme is expressed in about 90% of human tumors [5,11], have provided compelling arguments to indicate that the enzyme is a suitable cancer-associated target [36]. Data from preclinical studies on the effects of telomerase inhibition have led GRN163L (a.k.a.…”
Section: Preclinical Evidence Of Alt Activation As An Adaptive Responmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that telomerase-positive tumors often exhibit shorter telomeres than normal surrounding tissue counterparts [5], as a consequence of the late reactivation of telomerase activity during tumorigenesis [11]. This observation, alongside the evidence that the enzyme is expressed in about 90% of human tumors [5,11], have provided compelling arguments to indicate that the enzyme is a suitable cancer-associated target [36]. Data from preclinical studies on the effects of telomerase inhibition have led GRN163L (a.k.a.…”
Section: Preclinical Evidence Of Alt Activation As An Adaptive Responmentioning
confidence: 99%
“…Data from preclinical studies on the effects of telomerase inhibition have led GRN163L (a.k.a. Imetelstat), a palmitoyl lipid-based thiophosphoramidate oligonucleotide inhibiting telomerase activity through competitive inhibition [36], to enter clinical trials as a single agent or in combination with conventional anticancer drugs for different malignancies (https://clinicaltrials.gov). Available data have demonstrated that the drug has limited therapeutic efficacy, though it was generally well-tolerated and with common side effects, such as neutropenia, thrombocytopenia, anemia, fatigue, etc.…”
Section: Preclinical Evidence Of Alt Activation As An Adaptive Responmentioning
confidence: 99%
See 1 more Smart Citation
“…For further reading, we refer to a recent excellent article, which discusses this topic in greater detail [162]. Furthermore, we refer to a recent review article, which summarizes clinical trials on telomerase-based cancer therapeutics [163].…”
Section: Telomere and Telomerase-based Cancer Therapymentioning
confidence: 99%
“…Telomerase activity allows tumor cells to maintain the length of their telomere ends and escape replicative senescence; its regulatory role in metastatic events has also been proven. Many small molecule inhibitors of telomerase have been developed to date, however very few of them demonstrate significant antiproliferative or antitumor activity in vivo [ 15 ].…”
Section: Discussionmentioning
confidence: 99%